Pemetaan Fasilitas Umum dan Sosial sebagai Dasar Perencanaan Pembangunan di Desa Raku Kecamatan Tabukan Utara Kabupaten Kepulauan Sangihe Provinsi Sulawesi Utara - Sri Maryati; Muh Kasim; Fitrianingsih Antula; Riski I. Pidu; Rahmia Rahman; Delta Jexica Sianturi; Widya Candra Mooduto; Muhlis Ali; Aulia Fitrah Ramadhani; Mohamad Adrian Saputra; Aditya Prasetyo Mangkat; Abd. Rahman Maloho (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2022)
Economic growth and improvement the quality of life of good rural communities require the availability of adequate infrastructure and social public facilities. Infrastructure development in the village requires good planning, according to the needs of the community and according to the characteristics of each village. The results of field observations in Raku Village showed several findings, namely infrastructure and social public facilities were inadequate, there was no infrastructure distribution map, and the existing maps were not up to date. Mapping of public and social facilities in Raku Village, North Tabukan District, Sangihe Archipelago Regency, North Sulawesi Province is part of the community service activities of the Universitas Negeri Gorontalo Collaborative Real Work Lecture. The mapping of public and social facilities aims to map social public facilities, determine the distribution of public and social facilities, and provide spatial data as a basis for policy making by the government. Mapping of village public and social facilities which are part of this community service activity uses the integration method of field surveys and spatial data analysis. Data collection on the location of public and social facilities was carried out using an Android-based GPS, while information on public and social facilities was collected through interviews with residents. Processing and analysis of field survey data, both spatial data and attribute data, was carried out using the Geographic Information System software application, namely ArcGIS 10.8. The results of the primary data survey on public and social facilities and analysis of spatial data show that the public and social facilities in Raku Village are divided into educational facilities, religious facilities, health facilities, government offices, and other social facilities.